Are Medium-Sized Cities in China Shrinking from 2010 to 2020? An Empirical Analysis with a Multi-Dimensional Model - Lei Gao; Chao Ye; Liang Zhuang (Land, 2024)
Urban shrinkage has emerged as a worldwide concern, which is increasingly prevalent in developing countries like China, particularly in medium-sized cities (MSCs). Compared to large cities and counties, MSCs find themselves in a national policy blind spot and have been neglected both in policy and research. Previous studies, based on population changes, have shown that urban shrinkage in China is not severe. However, urban shrinkage is not just about population decline, and it has not been adequately discussed from a multi-dimensional perspective. This paper adopts a multi-dimensional model, considering population, economy, and space dimensions to analyze shrinkage patterns in 164 MSCs in China from 2010 to 2020. Findings reveal that 6.1% of MSCs experienced population shrinkage, and 24.4% faced shrinkage in economic or spatial dimensions. Shrinking MSCs are spatially distributed in the Northeast as well as in the areas surrounding large cities. Industrial restructuring, job losses, and healthcare disparities contribute to urban shrinkage, and the impact of aging will be further felt. As large cities consistently attract population and resources and digitization has dramatically affected population mobility, more MSCs will shrink in the future. This paper contributes to the understanding of shrinkage of MSCs among scholars and policymakers, urging a shift towards more balanced and digital urban governance.